Communicative-Pragmatic Directions of Contemporary Advertising Discourse - Kurpnijece, Rozanna (Respectus Philologicus, 2002)
The article deals with the analysis of discourse structures in advertising, discusses several aspects of interaction between psychological, communicative, and pragmatic components of advertising impact. The descriptive unit is an utterance manifested by a slogan on the textual level; the slogan is a pragmatic focus of advertisements. Advertising information is not homogeneous, but the fundamental component is included in a number of its basic parts forming a discourse space. Fundamental concepts as well as other information are enciphered; the research of this process leads to the integrative interpretation of discourse. Objectivization of the verbally expressed information in the advertisement is related to the procedures of activating cognitive structures and thinking operation, the processes that have been causing steady growing interest in modern linguistics.